Enhancing Worker Productivity through the S-O-R Theory in Human Resource Management - Taufik, Nuryanti; Supriadi, Apip; Ardiani, Gusti Tia; Komarlina, Dwi Hastuti Lestari (Jurnal Manajemen Teori dan Terapan| Journal of Theoretical and Applied Management, 2025)
Objective: This paper examines the influence of empowering leadership on positive worker behavior and work productivity in various organizational settings. Design/Methods/Approach: This study used a survey-based quantitative design with a causal predictive approach. Partial least squares-structural equation modeling (PLS-SEM) analysis was conducted on a research sample of 268 employees from various profit and non-profit organizations. Respondents were at least 18 years old. Findings: The findings reveal that empowering leadership positively relates to creative, collaborative, and innovative behavior. Creative and collaborative behavior affects positively to work productivity, whereas worker innovative behavior does not affect work productivity. Originality/Value: This study is one of the first to apply the S-O-R theory in the context of empowering leadership and its influence on positive worker behavior and work productivity. By using this framework, the research explores new dimensions of leadership impact in organizational behavior, offering valuable insights for human resource management in diverse settings. This research captures how empowering leadership (stimulus) influences employee behavior (organism) and subsequent work productivity (response). Practical/Policy implication: The result of this study is useful for HR managers seeking to enhance employee work productivity and innovation through leadership strategies. By adopting an empowering leadership style, HR managers can foster positive behaviors such as creativity and collaboration, which ultimately lead to higher organizational performance.